Hepatocellular Carcinoma in Delta Hepatitis Versus HBV Monoinfection: Spot the Differences - Razvan Cerban; Mirela Chitul; Speranta Iacob; Daria Gheorghe; Diana Georgiana Stan; Liana Gheorghe (Livers, 2025)
Background: Hepatitis delta virus (HDV) was recently proven to be directly carcinogenic on hepatocytes via different mechanisms compared to hepatitis B virus (HBV). Our study evaluated the differences between hepatocellular carcinoma (HCC) behaviour in both cases. Methods: A retrospective tertiary care centre study was conducted and included all HBsAg-positive adult patients admitted from the 1st of January 2021 to the 31st of December 2022. IBM SPSS 29.0 was used for statistics. Patients were split into a control group, HBV + HCC, and a study group, HBV + HDV + HCC. Results: A total of 679 patients were included, with an estimated prevalence of HCC in the HDV population of 20.8% versus 9.1% in the control group, p < 0.001, with an OR = 2.263 and a CI 95% of (1.536–3.333), p = 0.001. Younger patients developed HCC in the HBV monoinfection group (mean ± SD, 50.65 ± 12.302 years vs. 51.4 ± 13.708, p = 0.457). Study group patients had smaller tumours (maximum diameter: 32.66 ± 23.181 mm vs. 56.75 ± 38.09 mm, p = 0.002), lower AFP values (177.24 ± 364.8 ng/mL vs. 183.07 ± 336.77 ng/mL, p = 0.941) and predominantly loco-regional treatment. BCLC classification (p = 0.001) and the AFP-Duvoux score (p = 0.001) showed more advanced HCC in HBV monoinfection, with access to mainly systemic therapies (p < 0.001). Conclusions: HCC is more frequent in HDV-infected patients, leading to a different HCC pattern, with smaller tumours, less advanced neoplasia and less access to curative treatment compared to HBV-monoinfection-associated HCC.